What Is a Dingo? The Phenotypic Classification of Dingoes by Aboriginal and Torres Strait Islander Residents in Northern Australia - Brookes, Victoria J. (Animals (Basel), 2020)
SIMPLE SUMMARY: Dingoes are an Australian icon with cultural, as well as ecological, value, yet defining a dingo is complicated by hybridisation with domestic dogs. Northern Australia is a high-risk zone for the arrival of rabies, a disease which affects dogs (including dingoes) and people. In a rabies outbreak, Aboriginal and Torres Strait Islander peoples who live in this region would want dingoes protected. We visited the Northern Peninsula Area (NPA), Queensland, in 2018–2019 and surveyed Aboriginal and Torres Strait Islander residents about how they define dingoes, using pictures from camera traps previously placed and operated in the area. We found that dingo definition was based on characteristics traditionally associated with the iconic dingo (medium to large-framed dogs, with a long nose, pointed ears, narrow abdomen, bushy tail, smooth tan coats, and white feet and tail tip) but hybrid features, such as curled tail or a lack of white points, were also acceptable features. Local definitions are important when designing and implementing management plans so that actions are supported by local communities, and our findings are a useful guide for identifying dingoes in the NPA so that, in the event of a rabies outbreak, locally valued dingoes could be identified and protected. ABSTRACT: Dingo classification and management is complicated by hybridisation with domestic dogs. Northern Australia is a relatively high-risk zone for a rabies incursion, and in the event of an incursion, Aboriginal and Torres Strait Islander peoples who reside in this region would prioritise the protection of dingoes. Therefore, the classification of dingoes in this context is important. Twelve pictures of canids with features associated with both dingoes and domestic dogs from camera traps in the Northern Peninsula Area (NPA), northern Queensland, were shown to Aboriginal and Torres Strait Islander rangers (n = 3), biosecurity officers (n = 2), environmental health workers (n = 2), and residents (n = 39) in the NPA. Nearly all pictures (10/12) were classified as dingo or domestic dog (none as hybrid) and two were inconclusive (no overall agreement). Dingoes were consistently identified as medium to large-framed dogs, with a long nose, pointed ears, narrow abdomen, a bushy or feathered tail, and smooth coats of a single base colour. Some hybrid features were acceptable, including sable coats, lack of white tail tip or feet, and curled tail. These findings are a preliminary guide for identifying canids in the NPA region for whom management might be controversial. Building on this approach via further consultation with residents is needed to inform rabies response policy. Our approach using locally acquired camera trap pictures could also be extended to other regions in which dingoes have value but their management is controversial.